STOCK PRICE AND EXCHANGE RATE: THE CASE OF BIST 100 - Altin, Hakan (European Scientific Journal, ESJ, 2014)
Variations in the exchange rates concern all parts of the economy.One of those concerned topics is stock (share) prices and stock market indexes. In the study, the long term relationship between exchange rates and İstanbul Stock Exchange is analyzed. According to application results, there is a significant relationship between exchange rates and BIST 100. This result is consistent with Turkey’s foreign currency composition. However, the direction of the effect of foreign currencies on BIST 100 gives mixed results. In other words, the effect of each foreign currency on the stock index may be different. As a result, the existence of both short term and long term significant relationships between foreign currency markets and securities exchanges can be stated.